2018
DOI: 10.3389/fpsyt.2018.00282
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Between Treatment-Resistant and Non-Treatment-Resistant Schizophrenia Using Regional Homogeneity

Abstract: Background: Patients with treatment-resistant schizophrenia (TRS) and non-treatment-resistant schizophrenia (NTRS) respond to antipsychotic drugs differently. Previous studies demonstrated that patients with TRS or NTRS exhibited abnormal neural activity in different brain regions. Accordingly, in the present study, we tested the hypothesis that a regional homogeneity (ReHo) approach could be used to distinguish between patients with TRS and NTRS.Methods: A total of 17 patients with TRS, 17 patients with NTRS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…The abnormal regional spontaneous activities in the cuneus in the early stages of schizophrenia may cause higher-level cognitive impairments [51]. It was discovered that ReHo values decreased in right cuneus of patients with schizophrenia, which was partially consistent with previous findings [15,49]. We proposed that the disruption of the local synchronization of the spontaneous activities in these brain areas be related to the psychopathology of schizophrenia.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The abnormal regional spontaneous activities in the cuneus in the early stages of schizophrenia may cause higher-level cognitive impairments [51]. It was discovered that ReHo values decreased in right cuneus of patients with schizophrenia, which was partially consistent with previous findings [15,49]. We proposed that the disruption of the local synchronization of the spontaneous activities in these brain areas be related to the psychopathology of schizophrenia.…”
Section: Discussionsupporting
confidence: 78%
“…Regional homogeneity (ReHo) is a method employed in rs-fMRI and based on Kendall's coefficient of concordance to measure the temporal synchronization of the time series of each voxel and compare it with that of its adjacent neighbors [10]. Patients with SZ exhibit increased ReHo values in Dorsolateral Prefrontal Cortex (DLPFC) [11][12][13], medial prefrontal cortex [14], angular gyrus [15], precentral gyrus [16], and superior temporal gyrus [13] and decreased ReHo values in the superior temporal gyrus [13][14][15][16], occipital lobes [12,15,17], parietal lobule [14,16], precentral lobule [13,14], and postcentral gyrus [13,15,16]. A recent study showed positive correlations between attention function and mean ReHo values in the left middle frontal gyrus, right inferior/ middle temporal gyrus, angular gyrus, and inferior/superior parietal lobe in healthy control group, but no significant correlations were found in SZ group [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After initially removing the duplicates and browsing the title and summary, we found that 28 studies met the inclusion criteria, furthermore, after a detailed review of the full text, a total of 13 studies met the inclusion criteria. 8,9,11,12,[22][23][24][25][26][27][28][29][30] Figure 1 illustrates the identification and exclusion flow chart for the study. The included research reported ReHo differences in 511 schizophrenia (193 with FES and 318 with chronic schizophrenia), and compared with 452 HCs.…”
Section: Included Studies and Sample Featuresmentioning
confidence: 99%
“…Increased and decreased ReHo values represent abnormal neural activities (11). According to previous studies on subjects with a high risk of schizophrenia (12,13), first-episode adolescentonset drug-naïve schizophrenia (14,15), first-episode drug-naïve schizophrenia (16), chronic schizophrenia (17), and treatmentresistant schizophrenia (18), abnormal ReHo may be a good biomarker to distinguish patients with schizophrenia from healthy controls with increased or decreased ReHo values in different regions. However, previous results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%